Graphological Deviation on Instagram Captions (A Stylistics Study) - Gendis Iswara Paputungan; Nonny Basalama; Fahria Malabar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Language plays a crucial role in digital communication, and platforms like Instagram serve as key spaces for self-expression. This study investigates graphological deviations in Instagram captions, focusing on typography, spelling and grammar, and punctuation to understand their impact on written communication in social media. This research adopted a qualitative descriptive approach, analyzing captions from English Language Education Department students' Instagram accounts to identify and categorize graphological deviations. Data collection involved selecting captions with deviations in spelling, punctuation, and typography, followed by analysis using theories from Verdonk (2002) and Simpson (2004). The findings reveal that graphological deviations are intentionally employed to enhance aesthetics, convey emotions, and establish a relaxed, informal tone. Three main categories emerged: (1) Spelling and Grammar, which featured informal abbreviations and creative word formations and accounted for 10 instances; (2) Punctuation, where unconventional uses of quotation marks, ellipses, and dashes added emphasis and emotional depth, with 7 instances identified and (3) Typography, where unique fonts, emojis, and text layouts enhanced visual appeal, with 4 instances recorded. While such deviations may reduce clarity and professionalism, they significantly shape message reception in social media contexts. The study concludes that graphological deviations are a stylistic choice prioritizing aesthetics and emotional engagement over linguistic norms. Future research can explore their visual and emotional impact, typographic effectiveness, and multilingual adaptations in digital media.